Analysis of Learning Materials Aqidah Akhlak in Forming the Character of Student Discipline at MTs Al Fattah, Bekasi District - Illahi, Ahmas Ilham; Khoir, Abdul; Assiroji, Dwi Budiman (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to analyze the learning material of aqeedah morals in shaping the character of student discipline and the effect of aqeedah moral learning materials on the formation of students' disciplinary character. Data collection techniques used in this study include observation and interviews. Observations were made to directly observe student behavior in the context of learning aqeedah morals. Interviews were conducted with teachers and students to gain insight into how the learning materials affect the student's disciplinary character. Data analysis was performed using a qualitative approach. The results of this study indicate that learning materials for aqeedah morals have a significant influence in shaping the character of student discipline. Students learning good morals tend to show a higher level of discipline. It can be seen from the observation of student behavior, interview results, and questionnaire data, which show students' positive perceptions of the relationship between learning aqeedah morals and discipline. This research provides important implications for developing curriculum and learning practices to improve students' disciplinary character through the effective use of aqeedah akhlaq materials.